Pekanbaru City General Election Commission (KPU) Communication Strategy to Increase Political Participation of Beginner Voters in the 2024 Presidential Election - Risky Aris Nanda S; Sri Erlinda; Indra Primahardani (Journal of Education Technology Information Social Sciences and Health, 2024)
This research is motivated by KPU Regulation Number 10 of 2018 which contains methods of socialization in general elections carried out by the General Election Commission, both at central and regional levels. Of course, this KPU regulation can be a guide for the KPU in implementing strategies or ways to influence new voters to participate more actively in participating in the 2024 Presidential election. This research method is qualitative. The aim of this research is to find out the communication strategies used by the Pekanbaru KPU in increasing the participation of first-time voters in the 2024 presidential election. This research was carried out at the Pekanbaru KPU Office. To determine informants, the sampling method used was the Snowball sampling method. In this research, the researcher got 9 sources, including 2 KPU people, 5 PPK people, and 2 students from different schools. Based on the results of research with 9 sources, there are 4 strategies implemented by the Pekanbaru KPU in socializing the 2024 election, including face-to-face communication strategies, mass media communication strategies, props communication strategies, and creative media communication strategies. The strategy that was not implemented was the strategy of using democracy volunteers.